Maternal Characteristics Affect Fetal Growth Response to Maternal Supplements in the Women First Preconception Trial (WF) (P10-017-19) - Hambidge, Michael (Curr Dev Nutr, 2019)
OBJECTIVES: Determine if maternal characteristics modified newborn anthropometric outcomes in the WF trial (ClinicalTrials.gov NCT01883193). METHODS: Secondary analysis included combined data for all 1465 maternal infant dyads in WF sites in Guatemala, India, and Pakistan who had 1(st) trimester ultrasounds and newborn anthropometry with the three WF arms maintained: Arm 1 commenced a comprehensive nutrition supplement ≥3 months prior to conception; Arm 2 commenced the same supplement in the 1(st) trimester, and Arm 3 received no trial supplements. Maternal characteristics included were: baseline, BMI, hemoglobin, age, education, SES, and parity plus newborn sex. Newborn outcomes were Z-scores for length (LAZ), weight (WAZ), and weight-to-length ratio (WLRZ). Mixed effect regression models were fit for each outcome, including treatment arm, effect modifier, and treatment arm x effect modifier interaction as predictors and controlling for study site, maternal characteristics, and newborn sex. RESULTS: Parity, anemia and newborn sex were significant effect modifiers favoring para 0 vs para ≥1, anemia vs non anemia, and newborn male vs female. Effect of Arm 1 vs 3 was significantly larger for para 0 vs ≥1 women on length and weight (Table). Arm 2 vs 3 was not associated with improvements for para 0 in weight (P = 0.273) or WLRZ (P = 0.710). Arms 1 and 2 (vs 3) were associated with significantly higher length, weight, and WLRZ for anemic women. For parity and anemia, effect sizes for Arm 1 were greater than for Arm 2 for WAZ and WLZ (P < 0.05), but not LAZ. Arm 1 and 2 were associated with significantly higher weight and WLRZ for male vs female newborn. CONCLUSIONS: In diverse low resource populations, impaired fetal growth (weight and length) is substantially improved in nulliparous and in anemic women but minimally or not at all in parous and in non-anemic women. Correction of weight decrements is most pronounced with improvement in maternal nutrition commencing prior to conception. FUNDING SOURCES: Bill & Melinda Gates Foundation; NIH, NICHD and ODS. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: